Medical Stents
A tubular hydrogel stent with water-swelling properties addresses the challenges of SEMS removability and PS clogging by providing self-expandability, long-term patency, and economic benefits.
Patent Information
- Application Number
- JP2017229033
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2017-11-29
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2037-11-29
AI Technical Summary
Conventional self-expanding metal stents (SEMS) are difficult to remove due to tumor growth and require expensive shape memory alloys, while plastic stents (PS) prone to early clogging from protein adsorption in bile sludge, necessitating a stent that combines self-expandability, long-term patency, and easy removal.
A water-swellable tubular hydrogel made of hydrophilic polymers and water, utilizing water-swelling properties for self-expanding properties, reducing protein adsorption and enabling easy removal.
The tubular hydrogel stent maintains long-term patency with self-expanding capabilities and is economically advantageous, offering easy removal and reduced protein adsorption compared to conventional stents.
Smart Images

Figure 0007619542000002 
Figure 0007619542000003 
Figure 0007619542000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a tubular hydrogel and a medical stent. [Background technology]
[0002] Endoscopic biliary stenting (EBS) is widely used as the first-choice treatment for bile duct obstruction caused by lesions such as cancer and the associated obstructive jaundice and cholangitis (Non-Patent Documents 1 and 2). Stents used in such treatment procedures are broadly classified into self-expanding metal stents (SEMS) and plastic stents (PS).
[0003] Generally, SEMS secure a wide diameter in the bile duct by self-expansion driven by shape memory. Although SEMS are excellent in that they can maintain patency for a relatively long period of time, they are difficult to remove from the bile duct when restenosis occurs due to tumor growth or the like. Several methods have been proposed to improve the removability of SEMS, but they are not yet sufficient for practical use (e.g., Patent Documents 1 and 2). Another problem with SEMS is that they require expensive shape memory alloys.
[0004] On the other hand, PS is advantageous in that it is inexpensive and removable, and PS that has been given self-expanding properties by utilizing the shape memory properties of plastics has also been proposed (for example, Patent Document 3, Non-Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-129566 A [Patent Document 2] Registered Utility Model No. 3076346 [Patent Document 3] JP 2001-314517 A [Non-patent literature]
[0006] [Non-Patent Document 1] Biliary Tract, 29 (1), 31-37 (2015) [Non-Patent Document 2] Biliary Tract, 30(1), 43-50 (2016) [Non-Patent Document 3] App. Mater. Interfaces, 9 (16), 13988-13998 (2017) Summary of the Invention [Problem to be solved by the invention]
[0007] However, conventional PS is prone to adsorption of proteins contained in bile sludge, etc., and the inside of the duct becomes clogged early, so there is room for improvement in terms of maintaining long-term patency. SEMS and PS each have their advantages and disadvantages, and it is desirable to develop a stent that combines the advantages of both.
[0008] SUMMARY OF THE PRESENT DISCLOSURE An object of one aspect of the present invention is to provide a tubular molding material which has self-expanding properties and which, when used as a medical stent, can maintain patency for a long period of time and can be easily removed. [Means for solving the problem]
[0009] One aspect of the present invention provides a water-swellable, tubular hydrogel comprising a hydrophilic polymer and water.
[0010] The tubular hydrogel according to the present invention is endowed with the self-expanding property required for a stent by utilizing the water swelling property of the hydrogel as a driving force. Therefore, this tubular hydrogel exhibits the self-expanding property as a stent of a simple shape, and can be placed in the patient's body in a state that allows easy removal. In addition, since the hydrogel is hydrophilic, it is difficult for proteins to be adsorbed, and it is possible to maintain patency for a long period of time.
[0011] Another aspect of the present invention provides a medical stent comprising the above-mentioned tubular hydrogel. Effect of the Invention
[0012] According to the present invention, there is provided a tubular molding material that has self-expanding properties, and when used as a medical stent, can maintain patency for a long period of time and can be easily removed. Furthermore, since hydrophilic polymers are generally cheaper than shape memory alloys, a medical stent comprising the tubular hydrogel according to the present invention is advantageous in terms of economy compared to conventional SEMS. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a perspective view of one embodiment of a tubular hydrogel. [Diagram 2] 1 is a graph showing the relationship between the flexural modulus or swelling degree of a hydrogel and the water content. [Diagram 3] 1 is a graph showing the relationship between the tear strength or swelling degree of a hydrogel and the saponification degree of polyvinyl alcohol. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, several embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.
[0015] Fig. 1 is a perspective view showing one embodiment of a tubular hydrogel. Fig. 1(a) shows a tubular hydrogel 1 before swelling due to water absorption, and Fig. 1(b) shows a tubular hydrogel 1A after swelling.
[0016] The tubular hydrogel 1 before swelling contains a hydrophilic polymer and water, and has water swelling properties. In this specification, "water swelling properties" means a property of swelling with a swelling degree exceeding 0% by absorbing water. Details of the method for measuring the swelling degree will be explained in the examples described later. The swelling degree of the tubular hydrogel when it absorbs water may be, for example, 20% or more, 50% or more, 100% or more, 200% or more, 400% or more, or 1000% or more. In the case of a hydrogel used as a medical stent, it is desirable to express a swelling degree of 100% or more. The upper limit of the swelling degree is not particularly limited, but may be, for example, 2000% or less, or 400% or less.
[0017] The swelling degree of the hydrogel can be adjusted mainly based on the water content (the proportion of water based on the mass of the hydrogel before swelling). If the water content is low, the swelling degree tends to be high. Therefore, the water content can be set so as to obtain a desired swelling degree. Also, if the water content is high, the tear strength of the hydrogel tends to decrease. Therefore, in order to obtain a high swelling degree and an appropriate tear strength, the water content may be, for example, 60% by mass or less, 50% by mass or less, 40% by mass or less, or 30% by mass or less based on the mass of the tubular hydrogel. The water content may be, for example, 3% by mass or more based on the mass of the tubular hydrogel. If the water content is moderately high, the tubular hydrogel is likely to have an appropriate flexibility. A stent having an appropriate flexibility can be easily delivered endoscopically. From this viewpoint, the water content may be 13% by mass or more based on the mass of the tubular hydrogel.
[0018] The hydrophilic polymer may be any polymer capable of forming a hydrogel having water swelling properties, and examples thereof include polyvinyl alcohol, polyacrylamide, polyvinylpyrrolidone, and carboxymethylcellulose.
[0019] The polyvinyl alcohol may be a fully saponified type (saponification degree 100%) composed of only monomer units having a hydroxyl group, or may be a partially saponified type containing monomer units having an ester group such as an acetyloxy group (-OCOCH3). The saponification degree of the polyvinyl alcohol may affect the swelling degree of the hydrogel and the tear strength after swelling. The saponification degree of the polyvinyl alcohol may be 80% or more from the viewpoint of ensuring a high swelling degree, or may be 99% or less. From the viewpoint of high tear strength after swelling, the saponification degree of the polyvinyl alcohol may be 98% or more. In the case of a medical stent, it is desirable for the tear strength to be 1 N / mm or more from the viewpoint of removability, and a hydrogel having such a tear strength can be particularly easily obtained, for example, when the saponification degree of the polyvinyl alcohol is 80% or more. If the saponification degree is less than 80%, when the hydrogel absorbs water, the polyvinyl alcohol dissolves in the water, and the hydrogel may not be able to maintain its shape as a molded body. A PVA having a high degree of saponification (for example, a degree of saponification of 98% or more) may be combined with a PVA having a low degree of saponification (for example, a degree of saponification of 72.5 to 95.5%), and the average degree of saponification may be adjusted to fall within the above range. Since the tear strength is also affected by the moisture content, it is desirable to appropriately set the moisture content and the degree of saponification in order to obtain the desired tear strength.
[0020] The flexural modulus of the hydrogel forming the tubular hydrogel may be 1000 MPa or less from the viewpoint of flexibility required for endoscopic delivery as a stent, etc. The lower limit of the flexural modulus of the hydrogel is not particularly limited, but may be, for example, 0.01 MPa or more.
[0021] The hydrogel forming the tubular hydrogel may have a tear strength of 1 N / mm or more after swelling due to water absorption. A tubular hydrogel formed from a hydrogel that has a tear strength of 1 N / mm or more after swelling can usually have a strength that is not torn when removed. The upper limit of the tear strength is not particularly limited, but is usually about 20 N / mm or less.
[0022] The size of the tubular hydrogel 1 before swelling is not particularly limited, but the outer diameter may be 4.2 mm or less, or 0.5 mm or more. The thickness of the tubular hydrogel 1 before swelling is not particularly limited, but may be, for example, 0.05 to 1.5 mm. The length of the tubular hydrogel before swelling is not particularly limited, but may be, for example, 10 to 150 mm. Tubular hydrogels having these sizes are particularly suitable for, for example, medical stents.
[0023] The tubular hydrogel 1 can be produced, for example, by a method including filling a mold with a fluid gel precursor containing a hydrophilic polymer and water, freezing the gel precursor in the mold by cooling and then melting it to form a tubular hydrogel, and removing a portion of the water contained in the tubular hydrogel.
[0024] The gel precursor can be prepared, for example, by adding a precipitant to a polymer solution containing a hydrophilic polymer, and obtaining a precipitate containing the hydrophilic polymer and water as the gel precursor. The concentration of the hydrophilic polymer in the polymer solution may be, for example, 3 to 30% by mass based on the mass of the polymer solution. As the precipitant, an alkali metal salt such as sodium sulfate can be used. The mold in which the gel precursor is filled has a shape corresponding to the desired tubular hydrogel. The cooling temperature for freezing the gel precursor is, for example, -5°C or lower, and the temperature for melting the frozen gel precursor is, for example, 3 to 100°C. The hydrogel removed from the mold is heated under reduced pressure as necessary to remove a part of the water until a predetermined water content is reached. In other words, the hydrogel is dried. The heating temperature for removing the water is, for example, 15 to 200°C.
[0025] The hydrogel may be stretched while drying, which can impart swelling anisotropy by controlling the orientation of the hydrophilic polymer in the hydrogel.
[0026] A medical stent according to one embodiment includes the tubular hydrogel according to the above-described embodiment. This medical stent may be a clinical stent such as a bile duct stent, or may be used as an industrial material for surgical technique training. EXAMPLES
[0027] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.
[0028] Preparation of polyvinyl alcohol (PVA) gel Five types of powdered PVA (manufactured by Kuraray Co., Ltd.) with a degree of polymerization of 1,700 and a degree of saponification of 99.85% or more, 98.0-99.0%, 94.5-95.5%, 78.0-81.0%, or 72.5-74.5% were prepared. Each of these PVA powders was dissolved in ion-exchanged water by heating at 95°C for 1 hour to obtain a PVA aqueous solution with a concentration of 10% by mass. After stirring each of the PVA solutions after dissolution until it became homogeneous, they were mixed so that the average degree of saponification became the value shown in Table 1 to prepare a stock solution for gel preparation. A Na2SO4 solution with a concentration of 2 mol / kg was dropped into each stock solution to precipitate PVA. The resulting precipitate (gel precursor) was poured into a petri dish with a diameter of 40 mm or 60 mm. The precipitate on the petri dish was frozen at -30°C and then melted at room temperature to generate a circular sheet-shaped PVA gel (thickness: about 4-8 mm). The PVA gel was dried by heating at 60° C. for a time set between 0 and 120 hours to adjust the water content. By the above operations, PVA gels (hydrogels) of each example having different water contents or degrees of saponification were prepared.
[0029] Tear strength after swelling The PVA gel was immersed in physiological saline (NaCl concentration 0.9% by mass) until it was completely swollen. The tear strength of the swollen PVA gel was measured by a tensile test using a texture analyzer (manufactured by Eiko Seiki Co., Ltd., "TA XTPlus"). The tensile test was performed using a rectangular test piece 3 cm long and 1 cm wide cut out from the swollen PVA gel, hooked at positions 5 mm from the top and bottom ends of the test piece, and pulled at a speed of 1 mm / sec. The load at break was divided by the thickness of the PVA gel and recorded as the tear strength (N / mm). The tensile test was performed on three test pieces, and the average of the measured values was calculated.
[0030] Swelling degree The PVA gel cut into a size of 1 cm square was immersed in physiological saline (NaCl concentration 0.9% by mass, 37°C) for about 96 hours until it completely swelled. The swelling degree SR was calculated from the gel mass W0 (g) before swelling and the gel mass W1 (g) after swelling using the following formula. The same evaluation was performed on three test pieces, and the average of the measured values was calculated. Here, the complete swelling of the PVA gel was confirmed when the mass of the PVA gel did not change substantially. Usually, if the immersion time is 72 hours or more, the PVA gel can be considered to be completely swollen. SR(%)=[(W1-W0) / W0]×100
[0031] 3-point bending test The bending test was carried out using a texture analyzer (TA XTPlus, manufactured by Eiko Seiki Co., Ltd.). A rectangular test piece 25 mm wide and 5 cm long was cut out from the wet PVA gel before drying. The width, length and thickness of the cut out test piece were measured either as is or after drying at 60°C for 16 hours, 24 hours or 120 hours. The test piece was placed on a sample stand 25 mm wide, and a bending test was carried out at a speed of 1 mm / sec using a small three-point bending jig (HDP / 3PB, manufactured by Eiko Seiki Co., Ltd.). The bending modulus was calculated from the data in the initial linear region of the stress-strain curve using the following formula. The bending test was carried out on three test pieces, and the average value of the measured values was calculated. Flexural modulus (MPa) = (L 3F) / (4b h 3 ·Y) (MPa) Here, L is the width of the sample stage (mm), F is the stress (N), b is the width of the test piece (mm), h is the thickness of the test piece (mm), and Y is the strain.
[0032] moisture content Each PVA gel sample was dried under vacuum at 200°C for 12 hours using a vacuum dry oven (Tokyo Rikakikai, VOS-300SD). The mass W of the sample after completely removing water by drying was DRY The difference between the mass W0 of the sample before drying to completely remove the moisture was regarded as the mass of moisture, and the moisture content of each PVA gel was calculated from these values using the following formula. Measurements were carried out on three samples, and the average values were calculated. Water content=[(W0-W DRY ) / W0]×100
[0033] [Table 1]
[0034] The PVA gels of each Example exhibited water-swelling properties. In particular, the PVA gels of Examples 1 to 6 and 8, which had a water content of 60 mass % or less, exhibited a high degree of swelling of 100% or more.
[0035] Fig. 2 is a graph showing the relationship between the flexural modulus or swelling degree and the water content for Examples 4 to 7, in which the average saponification degree of PVA is 98.5%. Fig. 2 confirms that a higher swelling degree of 200% or more is achieved at a water content of 30% by mass or less, and that a moderate flexibility of a flexural modulus of 1000 MPa or less is obtained at a water content of 13% by mass or more.
[0036] Fig. 3 is a graph showing the relationship between the tear strength or swelling degree and the average saponification degree of PVA for Examples 2, 3, 5, and 8. From Fig. 3 and Example 1, it was confirmed that when the saponification degree of PVA is 80 to 99%, a particularly high swelling degree is easily obtained. Furthermore, it was also confirmed that when the saponification degree of PVA is 80% or more, a sufficient tear strength for a stent that can withstand removal of 1 N / mm or more is easily obtained.
[0037] <Animal experiments> As in Example 1, a precipitate formed from a PVA aqueous solution containing PVA with an average saponification degree of 86% was filled into a fluororesin jig (manufactured by Ito Machinery Co., Ltd.) forming a tubular mold. The precipitate in the jig was frozen at -30°C and then melted at room temperature to form a tubular PVA gel. The tubular PVA gel removed from the jig was heated at 60°C for 8 to 24 hours while being stretched, and dried to a state in which some moisture remained. The stretching ratio was 2 times. The tubular PVA gel after drying had an outer diameter of 2.5 mm or 3.5 mm, a thickness of 0.5 to 0.7 mm, and a length of 8 cm. The obtained tubular PVA gel was subjected to the following ex vivo evaluation and in vivo evaluation as a stent.
[0038] Ex vivo evaluation A bile duct was excised from live pig tissue purchased from Shibaura Organ Co., Ltd. A dry tubular PVA gel was inserted into the bile duct, immersed in saline, and the inner diameter was measured. The inner diameter expansion ratio was calculated by comparing the inner diameter before and after insertion, and was found to be 2 times, confirming that the gel had sufficient expandability as a stent.
[0039] In vivo evaluation To evaluate the handling property, a guide wire was passed through a colonoscope (channel diameter 4.2 mm) and the dried tubular PVA gel was inserted into the guide wire. The tubular PVA gel was pushed through the guide wire using an outer tube to evaluate the delivery property of the tubular PVA gel. The tubular PVA gel had good delivery property.
[0040] Next, a tubular PVA gel was orally placed as a stent in the biliary tract of a living pig under general anesthesia. When the PVA gel, which had swelled with body fluids during placement, was removed, it was confirmed that the PVA gel could be removed normally without breakage. [Explanation of symbols]
[0041] 1...tubular hydrogel, 1A...tubular hydrogel after swelling.
Claims
1. A self-expanding medical stent comprising a tubular hydrogel, The tubular hydrogel contains a hydrophilic polymer and water, the hydrophilic polymer comprises polyvinyl alcohol, and the average saponification degree of the polyvinyl alcohol is 80 to 99%, The water content of the tubular hydrogel is 30% by mass or less based on the mass of the tubular hydrogel. Medical stents.
2. The medical stent according to claim 1, wherein the tubular hydrogel exhibits a swelling degree of 100% or more when it absorbs water.
Citation Information
Patent Citations
Preparation of gel
JP1982130543A
Anti-thromotic medical material
JP1983121957A
Hydrogel interplantation matter in vessel
JP1994054854A
Composite tubular composition and device for medical use
JP1996267621A
Organism absorbing plastic stent and usage therefor
JP2001314517A